Selflessness as a universal neuropsychological foundation of spiritual transcendence: validation with Christian, Hindu, and Muslim traditions. Issue 2 (7th February 2017) - Johnstone, Brick; Hanks, Robin; Bhushan, Braj; Cohen, Daniel; Roseberry, Jarett; Yoon, Dong Pil
ABSTRACT: Research with US and European Christians has shown that increased spiritual transcendence is related to decreased right hemisphere/right parietal lobe (RH/RPL) functioning, which has been inferred as relating to increased "selflessness". To determine if RH/RPL selflessness is a universal neuropsychological foundation for spiritual transcendence across cultures and religions, this study evaluated 109 individuals with traumatic brain injury from the US and India, including Christians, Hindus, and Muslims. Participants completed measures of spiritual transcendence and spatial perception as an index of the functional integrity of the RH/RPL. Spearman correlations indicated that decreased RH/RPL functioning is significantly associated with increased spiritual transcendence for the entire sample, but not for different cultures or religions, likely due to decreased statistical power. The results suggest that decreased RH/RPL-related selflessness is a universal neuropsychological foundation for spiritual transcendence across cultures and faith traditions, which is interpreted individually based on cultural and religious background (e.g., closeness to God, Allah, and Brahman).